The concept of behavior in psychology: a historical and socio-cultural analysis - Polanco, Fernando (2016)
The concept of behavior is commonly used in our everyday speech. In the twentieth century, it became an important term because he began to take the place of the subject matter of the social sciences, particularly psychology. Therefore, we conducted an investigation where we analyze sociologically, historically and culturally the term behavior. Primary and secondary sources were reviewed. As a result, it is observed that the concept had two historical uses: a) as synonymous with character, with an emphasis of meaning in the moral and ethical; b) with the neutral use, as a verb, denoting an action or performance of an act. This last use was the one that had the greatest impact on the field of psychology. Its scope and dimensions were wide, having a central immutable idea, and a number of neighboring hypotheses in many ways in its different uses. The conclusion is to be defined in a necessary and objective not to generate conflicting uses in the scientific field, especially if this concept is part of the categories or objects of study.